Trajectories in the Discourse of Migration in Contemporary Britain (مجلة الواحات للبحوث والدراسات, 2025)
Immigration has always been one of the controversial topics in British politics and public policy. This paper will analyse two seminal trajectories in the discourse on and around immigration in the UK. The argument established here is concerned with major political attitudes in post-World War II towards Commonwealth immigration which are paralleled against the sceptic and uncertain attitudes vis-à-vis the free movement of Europeans across British borders. Westminster’s immigration policy is approached from the perspectives of discourse analysis. How were the discourses that sought to staunch the flow of immigration from the Commonwealth and Europe constructed in the political and public domains? It should be highlighted that this paper does not create a timeline or chronology of the British immigration policy, but rather hints to major language changes that reflect an adjustment in the discourse of immigration itself which, despite positive turnouts, remains racialized and suspicious of foreigners.Keywords: Immigration, Political Discourse, Discourse Analysis, Commonwealth, European Union.